A STUDY ON THE PHYSICAL DISABILITY AND BODY SATISFACTION THROUGH PHYSICAL ACTIVITY (Fiep Bulletin - online, 2011)
People with physical disabilities, most often, are considered far from ideal body type dictated by the standards of contemporary society, primarily by differences in their body, which normally are not accepted as ideal. Constantly, we see that some people with physical disabilities are excluded from social life did not fit the stereotype of the perfect body. This can cause changes in their body image, since the latter, as stated by Tavares (2003), is the mental representation of the body and identity is influenced by physiological, sociological and emotional. The aim of this study was to examine whether physical activity influences the level of satisfaction with body image of people with physical disabilities. Were 8 males with physical disabilities living in the city of Juiz de Fora / MG. All reported that they are physically active with weekly average of 2.63 (± 1.598). The average age of those assessed is 30.63 (± 9.303). Finally, we can see that although body dissatisfaction has been shown to be recurrent in this study, physical activity is identified by most participants as a major factor in the development of satisfaction with body image. According to Tavares (2007) physical education may be one of the possibilities for the full development of body image. It can be emphasized by means of leisure, play, dance, recreation, arts body in general as well as the pursuit of discovery and quest for acceptance and overcoming limits.
Keywords: Body Image; Body Satisfaction; Physical Disability